Argeneau : A Quick Bite - Book 1 Book 1 - Sands, Lynsay (New York : Avon Books, 2005)
Lissianna Argeneu is a vampire who hates the sight of blood. Yet she feels a different kind of hunger for psychoanalyst Greg Hewitt.
Keywords: Vampires -- Fiction